A Case of Postmalaria Neurologic Syndrome and Pediatric Literature Review. Issue 10 (October 2020) - Faivre, Benjamin; Bessis, Simon; Bergounioux, Jean; Duran, Clara; Dinh, Aurélien; Essid, Aben
Abstract : Postmalaria neurologic syndrome is an under-recognized self-resolving acute neuropsychiatric condition, usually occurring after complete recovery from malaria. We describe the case of a 7-year-old child who presented with an afebrile lymphocytic meningoencephalitis. The notion of a previously treated malaria episode and the absence of malaria during current episode led us postmalaria neurologic syndrome diagnosis with secondary spontaneous outcome.